PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS X SMAN 3 KUPANG - Bulla, Erna Theresia; Djawa, Alex; Ga, Susana (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
Abstract This research aims to improve the speaking skills of class X students through the application of the Problem Based Learning (PBL) learning model. The focus of the problems that occur in learning Indonesian at SMAN 3 Kupang is the lack of interest and active participation of students, which causes learning outcomes below the Minimum Completeness Criteria (KKM). This research uses the Classroom Action Research (PTK) method with two cycles, including planning, action, observation and reflection stages. In cycle I, learning results showed an average score of 71.67 with classical completeness of 50%, where only 18 out of 36 students achieved a score ≥75. After improvements in cycle II, the average score increased to 90 with classical completeness of 92%, where 33 out of 36 students achieved a score ≥75. This increase shows that the implementation of PBL is effective in improving students' speaking skills. Students' active participation and involvement in the learning process also increased significantly. This research concludes that the Problem Based Learning model assisted by LKPD can improve Indonesian language learning outcomes and speaking skills for class X students at SMAN 3 Kupang. Keywords: LKPD, Negotiation Text, Problem Based Learning (PBL)